Benzothiazole hydrazones of furylbenzamides preferentially stabilize c-MYC and c-KIT1 promoter G-quadruplex DNAs. Issue 24 (29th March 2016) - Pany, Sushree Prangya Priyadarshinee; Bommisetti, Praneeth; Diveshkumar, K. V.; Pradeepkumar, P. I.
Abstract : The stabilization of G-quadruplex DNA structures by using small molecule ligands having simple structural scaffolds has the potential to be harnessed for developing next generation anticancer agents. Abstract : The stabilization of G-quadruplex DNA structures by using small molecule ligands having simple structural scaffolds has the potential to be harnessed for developing next generation anticancer agents. Because of the structural diversity of G-quadruplexes, it is challenging to design stabilizing ligands, which can specifically bind to a particular quadruplex topology. To address this, herein, we report the design and synthesis of three benzothiazole hydrazones of furylbenzamides having different side chains (ligands1, 2 and3 ), which show preferential stabilization of promoter quadruplex DNAs ( c-MYC and c-KIT1 ) having parallel topologies over telomeric and duplex DNAs. The CD melting study revealed that all the ligands, in particular ligand2, exhibit higher stabilization toward parallel promoter quadruplexes (Δ T m = 10–15 °C) as compared to antiparallel promoter quadruplex ( h-RAS1 ), telomeric quadruplex and duplex DNAs (Δ T m = 0–3 °C). FID assay and fluorimetric titration results also reveal the preferential binding of ligands toward c-MYC and c-KIT1 promoter quadruplex DNAs over telomeric and duplex DNAs. Validating these results further, Taq DNA polymerase stop assay showed IC50 ∼ 6.4 μM for ligand2 with the c-MYC DNA template, whereas the same for the telomeric DNA template was found to be >200 μM. Molecular modeling and dynamics studies demonstrated a 1 : 1 binding stoichiometry in which stacking and electrostatic interactions play important roles in stabilizing the c-MYC G-quadruplex structure. Taken together, the results presented here provide new insights into the design of structurally simple scaffolds for the preferential stabilization of a particular G-quadruplex topology.